Pediatric SOFA score for detecting sepsis in children - Muhammad Aulia; Silvia Triratna; Yulia Iriani; Achirul Bakri; Indra Saputra (Paediatrica Indonesiana, 2021)
Background The pediatric logistic organ dysfunction-2 (PELOD-2) score is recommended by the Indonesian Pediatric Society Emergency and Intensive Care Working Group as an indicator of life-threatening organ dysfunction for sepsis in children. However, The Third International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3) recommended the Sequential (Sepsis-related) Organ Failure Assessment (SOFA) score in determining life-threatening organ dysfunction, which has not been adjusted for pediatric patients. Objective To assess the accuracy of the pediatric SOFA score in diagnosing sepsis in children admitted to the pediatric intensive care unit (PICU) at Mohammad Hoesin Hospital, Palembang, South Sumatera. Methods The study was conducted in children with organ dysfunction caused by infection admitted in PICU, from April to December 2019. Subjects were included by consecutive sampling, according to the following inclusion criteria: all patients aged 1 month to 18 years who met organ dysfunction and two SIRS criteria, with infection according to the 2005 PSCC criteria. Laboratory tests performed included complete blood count (CBC), blood gas analysis, measurement of C-reactive protein (CRP), liver and kidney function tests. In all patients, pSOFA and PELOD-2 scores were calculated within 24 hours of admission. We compared the accuracy of pSOFA score to PELOD-2 score >= 11. Results Of 108 subjects, there were 59 males and 49 females, with median age 11 (range 1-193) months. We compared the accuracy of pSOFA score to PELOD-2 score >= 11 and obtained a sensitivity of 93.3% and a specificity of 79.5%, for pSOFA cut-off score ? 8. Pediatric SOFA score cutoff >= 8 was determined by receiver operating curve (ROC). The area under the curve (AUC) for pediatric SOFA score was 93.9% (95%CI 89.7 to 98.0%). Conclusion Pediatric SOFA score >= 8 is the optimal cut-off for predicting life-threatening organ dysfunction in pediatric sepsis. Multicenter revalidation is needed to find the most optimal cut-off point for general use in Indonesia.